Predictive diagnosis of familial adenomatous polyposis with linked DNA markers: population based study. Issue 6831 (4th April 1992) - MacDonald, F.; Morton, D. G.; Rindl, P. M.; Haydon, J.; Cullen, R.; Gibson, J.; Neoptolemos, J. P.; Keighley, M. R.; McKeown, C. M.; Hultén, M.
Abstract : OBJECTIVES--To evaluate the use of polymorphic DNA probes linked to the APC gene in the presymptomatic diagnosis of familial adenomatous polyposis. DESIGN--Four DNA probes were tested on an unselected population of patients at risk of familial adenomatous polyposis. SUBJECTS--The first 47 families notified to the West Midlands familial adenomatous polyposis register. Plus five families sent to our hospital as part of the West of Britain DNA consortium. MAIN OUTCOME MEASURES--The proportion of families and family members in whom DNA testing could be used to adjust the estimate of risk. RESULTS--Only 17 families on the register (containing 46% (74/162) of the population at risk) had a suitable pedigree structure for DNA analysis. DNA was analysed in 12 of these families plus the five families from the West of Britain consortium. At least one probe was informative in 27 of the 33 subjects born with 50% risk, but the most informative probe (pi 227) was the one with the highest recombination rate (10%). Flanking markers were informative in only four of the 33 subjects. CONCLUSIONS--These findings confirm the potential for accurate predictive diagnosis of familial adenomatous polyposis with polymorphic DNA probes, but such an approach is currently limited to about one third of affected families. A combined approach to presymptomatic diagnosis, which includes DNA testing and indirect ophthalmoscopy, is advocated.